STRUCTURAL EQUATION MODEL OF TEACHERS' MINDSETS, SELF-EFFICACY, AND EMOTIONAL EXPERIENCES AND IRANIAN EFL LEARNERS' WILLINGNESS TO COMMUNICATE AND L2 MOTIVATIONAL SELF SYSTEM - Amirian, Zahra; Shayanfar, Mitra; Rezazadeh, Mohsen (Journal of Languages and Language Teaching, 2021)
This study aimed at investigating the interrelationships between EFL teachers' mindsets, self-efficacy, and emotional experiences and Iranian EFL learners' willingness to communicate (WTC) and L2 motivational self system (L2MSS). The participants of this study were 100 Iranian teachers and 501 students of the same EFL teachers, both male and female randomly selected from high schools. To fulfill the purpose of the study, teachers were asked to complete four questionnaires to measure their implicit theories of intelligence, efficacy, and emotional experiences including their burnout symptoms. Learners were required to complete two questionnaires to measure their willingness to communicate and L2 motivational self system. The results of Structural Equation Modeling (SEM) revealed a significant structural relationship among all variables. Results also indicated that motivation was the strongest direct predictor of willingness to communicate. WTC was also indirectly correlated with teachers' implicit theories, efficacy, and emotional experiences through the mediating effect of L2MSS.Â